2019
DOI: 10.1002/ccd.28433
|View full text |Cite
|
Sign up to set email alerts
|

A head‐to‐head comparison of three coronary fractional flow reserve measurement technologies: The fractional flow reserve‐device study

Abstract: Objectives: To compare three FFR technologies: the electric-sensor Pressurewire ® (P), the optic-sensor Comet ® (C) guidewire, and the optic-sensor Navvus ® (N) microcatheter.Background: Different technologies are used to measure fractional flow reserve (FFR) for the functional assessment of coronary lesions with potential discrepancies.Methods: Sixty-six FFR measurements performed on 32 lesions using each technology were used for a paired comparison of FFR on simultaneous measurements and in clinically releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In this study, MEMS‐PMC has the same device success rate as PW (97.5 vs. 96.3%, p = .43), and all MEMS‐PMCs successfully crossed the lesions. The success results of optical‐sensor PMC are similar: 97% (94/97, CONTRACT), 30 97% (237/245, ACIST‐FFR), 14 97% (972/1000, pre‐PCI, FFR‐SEARCH) 11 and 94% (31/33, FFR‐DS) 29 . During the study, no thrombus was observed on the devices in any of the enrolled 242 patients, nor was there any other serious adverse event.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…In this study, MEMS‐PMC has the same device success rate as PW (97.5 vs. 96.3%, p = .43), and all MEMS‐PMCs successfully crossed the lesions. The success results of optical‐sensor PMC are similar: 97% (94/97, CONTRACT), 30 97% (237/245, ACIST‐FFR), 14 97% (972/1000, pre‐PCI, FFR‐SEARCH) 11 and 94% (31/33, FFR‐DS) 29 . During the study, no thrombus was observed on the devices in any of the enrolled 242 patients, nor was there any other serious adverse event.…”
Section: Discussionmentioning
confidence: 68%
“…The success results of optical‐sensor PMC are similar: 97% (94/97, CONTRACT), 30 97% (237/245, ACIST‐FFR), 14 97% (972/1000, pre‐PCI, FFR‐SEARCH) 11 and 94% (31/33, FFR‐DS). 29 During the study, no thrombus was observed on the devices in any of the enrolled 242 patients, nor was there any other serious adverse event. Thus, the MEMS‐PMC is safe to use for routine clinical FFR measurement.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In this issue of Catheterization and Cardiovascular Interventions , Beygui et al measured FFR on 32 lesions with 50–75% stenoses in patients with stable ischemic heart disease, and compared measurements obtained using three different systems: PressureWire (Saint Jude Medical, St. Paul, MN), Comet wire (Boston Scientific, Plymouth, MN), and Navvus microcatheter (ACIST, Eden Prairie, MN) 3 . The study design included the use of intracoronary adenosine to achieve maximal hyperemia, measurements of FFR with each device alone and in combination with another device, and assessment of pressure drift.…”
mentioning
confidence: 99%